SISTEM INFORMASI MONITORING ASET ELEKTRONIK BERBASIS WEB PADA DIREKTORAT JENDRAL KETAHANAN DAN PENGEMBANGAN AKSES INDUSTRI INTERNASIONAL KEMENTRIAN PERINDUSTRIAN REPUBLIK INDONESIA - Cut Alanda Deshire, - (2018)
Asset management in an organization is an important thing to do. Listing of assets owned by an organization is a major process and is very important to do in recording data assets owned by the organization. The existence of exact information about assets owned by an organization will make it easier for the organization, so that will be able to optimize the use of those assets. The new Directorate General of Resilience and Development of International Industrial Access was formed on 16th of 2014 through Presidential Regulation No. 29 of 2015 on the Ministry of Industry, still conducting the process of recording its assets in electronically manual so that the process and the results are not maximize yet. This study designs a web-based electronic monitoring information system that has features that can record detailed attribute information and monitor and map the location of existing assets. Through a web-based monitoring information system, the implementation of monitoring of various assets, especially electronics can be done easily and practically